Peningkatan Kompetensi TPACK Guru Melalui Pelatihan Pengembangan Media Pembelajaran Berbasis Augmented Reality - Rahmatullah, Basith; Kadarwati, Irma (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
The aim of this research is to assess the effectiveness of an Augmented Reality-based instructional media development training model in enhancing teachers' competencies to develop and utilize Augmented Reality-based instructional media. The 4D research and development model consist of four stages: define, design, develop, and disseminate. The current situation presents an opportunity for teachers to optimize the presence of smartphone technology and mobile devices by integrating traditional methods with technological approaches in education. The integration of smartphones or mobile devices with traditional teaching aids such as print media (books, posters, etc.) brings about innovations in instructional media, known as Augmented Reality. To implement and enhance Augmented Reality-based instructional media, teachers need knowledge in planning and developing such media to create engaging digital-based learning experiences. Data analysis in this developmental research is conducted pre-training, during training, and post-training. Assessing the improvement in participants' learning outcomes requires initial and final test data. The initial test scores yielded an average of 58.7, while the final test scores showed an average of 81.8, indicating a 39% increase in test scores. Encouraging active involvement of teachers in professional development programs or competency enhancement training is crucial in advancing the use of technology in education.